Work Environment, Work Ability and Work Discipline in Improving Employee Performance - Soni Suharmono; Normansyah Normansyah; Wira Pramana Putra; Ridwan Ridwan (Yayasan Riset dan Pengembangan Intelektual, 2023)
Organizations can be developed because of the role of human resources. They are executors of all organizational activities. Qualified human resources must be recruited so that the organization can achieve its target. The basic problem in the sub district office is how to spur employee performance to always improve. Excellent employees will contribute significantly to achieving the institution's goals. This study aims to analyze and examine the factors influencing employee performance at the Pringgasela District Office, East Lombok. These factors include work environment, work ability and work discipline. The research used the quantitative with regression analysis method. The data was collected using questionnaires distributed to all employess Pringgasela District Office. The sampling method used is census sampling technique with a total population of 32 employees. The data were analyzed with IBM SPSS version 21 and analysis was carried out by several tests such as validity test, reliability test, classic assumption test, linear regression analysis and coefficient of determination test. The results of this study indicate that partially, work environment, work ability and work discipline have a positive and significant effect on employee performance. Simultaneously, work environment, work ability and work discipline have a positive and significant effect on employee performance at the Pringgasela District Office, East Lombok. The findings can be a reference for government in the district area in order to improve employee performance that has a good impact on the quality of public services to the citizens.